REPRESENTASI SASTRA ARAB DI KAWASAN ASIA TENGGARA - Sulfikar, Sulfikar; Zuhdy, Halimi; Fawzani, Nurul; Amri, Tasdieq Ulil (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2023)
Literature becomes part of a cultural entity whose practice is reflected in literary works. Along with the times, the existence of Arabic literature spread to various continents including Southeast Asia. Arabic literature is one of the supporting factors in the spread of Islam, especially in Southeast Asia. The purpose of this research is to understand the existence of Arabic literature and its forms in the Southeast Asian region. This research uses a type of library research through a qualitative approach. Sources of data in this study were secondary, namely articles, books, and research reports on Arabic literature in the Southeast Asian region. Data collection techniques in this study used documentation techniques. The collected data were then analyzed using a descriptive method by describing findings related to the existence and forms of Arabic literature in the Southeast Asian region. The results of the study show that the history of Islamization in Southeast Asia has left behind a wealth of written texts, both literary and religious, in large numbers. The use of Malay Arabic script in several countries in Southeast Asia is a reflection that Arabic literature exists in Southeast Asia.